SISTEM PAKAR MENDIAGNOSA PENYAKIT GIGI DAN MULUT SERTA KEBUTUHAN PERAWATNNYA - Kusnanto, Gery; Habib, Ahmad; Ardiyanti, Christin (KONVERGENSI, 2015)
Dental disease is the most often disease which is complained by Indonesian people due to the passiveness  of dental  healthy.  A person’s  dental healthy  obviously  takes impact  to others organs  and up until  now  dental  healthy  not being  the main concern  yet. Therefore,  it is required an application  which could assist dentist and assistant’s work in diagnosing  and providing  beneficial information to the people about the important of dental healthy. That application is in the form of expert system by using forward chaining method. Expert system diagnoses   dental   disease   and  mouth   including   the  treatment   needed.   Hopefully   this application could assist people in diagnose dental disease and mouth, so that could resulting the precise way of healing along with giving dental health information about the way to treat dental properly.Keywords : Encyclopedia, Historic Buildings, Android.